Analisis Keamanan Data Pengguna pada Platform E-commerce: Studi Kasus Kebocoran Data Tokopedia 2020 - Naila Zafira; Nabila Aisyahara; Cut Aidila Safriana; Rofli Rofli; Hafizatunnisa Hafizatunnisa (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid growth of e-commerce platforms has increased the collection and processing of users’ personal data, which consequently raises security risks. One of the most significant incidents in Indonesia was the Tokopedia data breach in 2020. This study aims to analyze user data security issues on e-commerce platforms through a case study of the Tokopedia data breach. The research method uses a descriptive qualitative approach based on literature review and secondary data analysis. The results indicate that data breaches are influenced not only by technical vulnerabilities but also by weaknesses in data governance and security management. This study also reviews the incident from a legal perspective based on Indonesia’s Personal Data Protection Law. The findings are expected to contribute to improving data security practices on e-commerce platforms.